2015
DOI: 10.1016/j.juro.2015.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in the Wnt/β-Catenin Signaling Pathway as Indicators of Bladder Cancer Risk

Abstract: Purpose The genetic factors that influence bladder cancer risk remain largely unknown. Previous research has suggested that there is a strong genetic component underlying the risk of developing bladder cancer. The Wnt/β-catenin signaling pathway is a key modulator of cellular proliferation through its regulation of stem cell homeostasis. Furthermore, variants in the Wnt/β-catenin signaling pathway have been implicated in the development of other cancers leading us to believe this pathway may play a vital role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…In BC tissues, mutations or genetic changes in the regulatory pathway of Wnt/β-catenin signaling resulted in EMT, the emergence of urothelial CSC phenotype, chemoresistance, enhanced survival, and the promotion of tumorigenesis [79]. In urothelial CSCs, the genotyping of single nucleotide polymorphisms of 40 genes in the Wnt/β-catenin signaling pathway revealed variants in the Wnt/β-catenin stem cell pathway that were proven to have a role in the pathogenesis of BC [80]. Another report also showed that the accumulation of β-catenin and dysregulation of the Wnt/β-catenin pathway induced neoplastic proliferation and increased the potential of invasion in BC [81].…”
Section: Wnt/β-catenin Pathwaymentioning
confidence: 99%
“…In BC tissues, mutations or genetic changes in the regulatory pathway of Wnt/β-catenin signaling resulted in EMT, the emergence of urothelial CSC phenotype, chemoresistance, enhanced survival, and the promotion of tumorigenesis [79]. In urothelial CSCs, the genotyping of single nucleotide polymorphisms of 40 genes in the Wnt/β-catenin signaling pathway revealed variants in the Wnt/β-catenin stem cell pathway that were proven to have a role in the pathogenesis of BC [80]. Another report also showed that the accumulation of β-catenin and dysregulation of the Wnt/β-catenin pathway induced neoplastic proliferation and increased the potential of invasion in BC [81].…”
Section: Wnt/β-catenin Pathwaymentioning
confidence: 99%
“…The core regulatory factors of endometrial cancer and pancreatic cancer have quite a lot of crosstalk and overlap. Take β -catenin as an example, β -catenin has been revealed to participate in the Wnt signaling pathway in various tumor subtypes [55, 56]. The initiation and progression of both pancreatic cancer and endometrial cancer have been confirmed to be associated with Wnt signaling pathway, implying that such two regulatory networks may have crosstalk and our extracted KEGG pathway (hsa05213) may actually contribute to the progression of pancreatic cancer [5759].…”
Section: Resultsmentioning
confidence: 99%
“…The Wnt/β-catenin signaling pathway, also known as the canonical Wnt pathway, is closely associated with malignant transformation of cancer cells and metastasis (21,22). In addition, the Wnt/β-catenin pathway has been demonstrated to be involved in the development of bladder cancer (23). The present study aimed to investigate whether ZBTB38 can promote the migration and invasive growth of bladder cancer cells, and to identify the possible effects of ZBTB38 on the Wnt/β-catenin signaling pathway.…”
Section: The Role Of Zbtb38 In Promoting Migration and Invasive Growtmentioning
confidence: 99%